The Influence Of Board’s Human Capital And Social Capital Towards Firm Performance In Asian Tourism Industry - Ooi, Chai Aun (2014)

(untitled)
This study examines the relationship between firm performance and board diversity in human capital and social capital in the context of the tourism industry. Human capital is represented by educational background and working experience of the board of directors; social capital is represented by external network ties via interlocking directorates of the board of directors. 85 tourism firms from the four economies in Asia, namely China, Hong Kong, Malaysia and Singapore are selected. This sample period of analysis is 2001-2011. Kajian ini mengkaji hubungan antara prestasi firma and kepelbagaian modal insan dan modal sosial lembaga pengarah, dalam konteks industri pelancongan. Modal insan merujuk kepada latar belakang pendidikan serta pengalaman pekerjaan pengarah, manakala modal sosial merujuk kepada jaringan luar pengarah melalui pegangan jawatan pengarah di firma yang lain. Sebanyak 85 firma pelancongan dari empat buah ekonomi di Asia, iaitu China, Hong Kong, Malaysia dan Singapora telah dikaji. Tempoh kajian merangkumi tahun 2001-2011.